Sans hommes, on n’est pas rien”: Defying Patriarchy and Reclaiming Voices in Les Rivières - Warisara E Sawin (Vernacular: New Connections in Language, Literature, & Culture, 2024)
This article explores Jennifer Solheim’s conceptualization of “the call to listen” in postcolonial Francophone cultural production, as she argues for the importance of engaging with and responding to immigrant and minority narratives within this cultural milieu. This article further explores the dynamic relationship between media consumption and artistic creation, specifically the innovative realms of “accented” and “intercultural” cinema that have emerged from the conditions of globalization and migration. The unique cinematic languages of these forms convey the intricate experiences of those living in exile or as part of post-migratory populations. An in-depth analysis is presented on Mai Hua’s documentary Les Rivières (2020), which interweaves “women’s poetics” with a critique of patriarchal society. Hua’s narrative offers a moving exploration of familial trauma and the pursuit of identity, contextualized within the broader discourse on female representation in film and media. This article demonstrates how the documentary aligns with the concept of the female gaze and écriture féminine, asserting the significance of a genuine female narrative space. Conclusively, the article underscores the documentary’s capacity as an archival resource, a testament to personal and communal histories, and as a medium that transcends cultural boundaries. It highlights the documentary’s global impact and its role in fostering visibility and empowerment for marginalized groups, thus contributing to a richer understanding of gender and human experience across diverse cultures.
Keywords: post-migratory postcolonial; Viet Kieu; documentary; transcultural trauma